Early taurine administration as a means for halting the cytokine storm progression in COVID-19 patients - Alberto Rubio-Casillas; Ramesh C. Gupta; Elrashdy M. Redwan; Vladimir N. Uversky; Raied Badierah (Open Exploration Publishing Inc., 2022)
Around the world, more than 6.2 million individuals have died as a result of coronavirus disease 2019 (COVID-19). According to a recent survey conducted among immunologists, epidemiologists, and virologists, this disease is expected to become endemic. This implies that the disease could have a continuous presence and/or normal frequency in the population. Pharmacological interventions to prevent infection, as well as to treat the patients at an early phase of illness to avoid hospitalization are essential additions to the vaccines. Taurine is known to inhibit the generation of all inflammatory mediators linked to the cytokine storm. It can also protect against lung injury by suppressing increased oxidants production and promoting the resolution of the inflammatory process. Neutrophil lactoferrin degranulation stimulated by taurine may have antiviral effects against SARS-CoV-2, limiting viral replication. It is hypothesized that if taurine is administered early in the onset of COVID-19 disease, it may stop the cytokine storm from progressing, lowering morbidity and mortality.